Inclusion of Climate Smart Agriculture (CSA) technologies and investment in Bhutan's Agricultural Development Plan to 2040 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The Ministry of Agriculture and Forests (MoAF) in 2018 initiated the process of envisioning the strategic long-term vision for agriculture development aligned to evolving paradigm of political, social, economic, and environmental dynamics. Distinguishing the profundity and excellence of past engagement of the International Food Policy Research Institute (IFPRI) with MoAF since 2005 in food and nutrition analyses, in 2018 the Ministry approached IFPRI for the technical support in crafting the Renewable Natural Resource (RNR) Strategy.